Research measurement of knowledge advances in building maintenance issues. Issue 1 (8th April 2014) - Falorca, Jorge; Calejo Rodrigues, R.; Mendes da Silva, R.
Abstract : Purpose: – The purpose of this paper is to assess the general progress of Building Maintenance knowledge, to ascertain the growth of the whole body of literary production, and to determine which research lines may require further development. Design/methodology/approach: – Using several means of support, a detailed survey of over 2, 000 titles of publications was made. The survey data were grouped into six pre-defined bibliographic indicators. The survey results were gradually organized into a database and MS Excel features were used for the subsequent process of counting and statistical analysis. Findings: – The results allowed the authors to develop an approximate growth model of the literature and provided indications of possible gaps in the development of knowledge. Research limitations/implications: – To allow for a more extensive analysis of the problem, this study was structured differently to a traditional literature review. Practical implications: – This study offers an overview of the evolution of building maintenance literature to researchers and institutions. A dynamic bibliographic database was also created which could be useful for those who perform management functions. Originality/value: – The approach of this study differs from other known studies in the area of building maintenance. This study releases an approximate measurement of advances made in the knowledge of a particular subject.